A Parte no partido: relações de poder e política na formação do estado nacional brasileiro, na província do Ceará (1821-1841). - Araújo, Reginaldo Alves de (2018)
The constitutionalism promoted by the Porto Revolution, at the dawn of the 1820s, spread and popularized a new political language, that until then circulated very little, due to the prohibitions imposed by the colonial government. Concepts such as political representation, popular sovereignty, legal equality, among others, linked to the Enlightenment tradition, have suddenly become commonplace subjects in the sermons of the priests and in the rhetoric of local lords. Printed on the pages of the newspapers and read aloud on the porches of houses in the presence of slaves and clusters, the new ideas of constitutionalism arrived with force in Ceará in the 1820s. In this context, a group of merchants and bureaucrats from Fortaleza, as well as other towns in the province of Ceará, saw an opportunity there to create a government that would serve their interests. With the intention of occupying the provincial administrative positions, as well as of being elected to the national parliament (first in Lisbon, later in Rio de Janeiro), this provincial elite tried to extend its relations of alliances, through the practices of exchange of favors, resorting to the patronage practices of the colonial phase. On the other hand, disputes over the power spaces between the members of the local lords led not only to the formation of alliances, but also to rancor and rivalry between houses. The so-called provincial political parties were born, characterized as alliances surrounding an influential political personality, gaining significant advantages for themselves and their group, in exchange for the guarantee of favorable results in the elections and the persecution of the local enemies. Through this, the present thesis presents as a problem the formation of the Brazilian national state, in the province of Ceará, addressing the role of the local elite during the process.